2019
DOI: 10.3390/ijms20122898
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Based Analysis Reveals a Crucial Role of BxGPCR17454 in Low Temperature Response of Pine Wood Nematode (Bursaphelenchus xylophilus)

Abstract: Background: The causal agent of pine wilt disease is the pine wood nematode (PWN) (Bursaphelenchus xylophilus), whose ability to adapt different ecological niches is a crucial determinant of their invasion to colder regions. To discover the molecular mechanism of low temperature response mechanism, we attempted to study the molecular response patterns under low temperature from B. xylophilus with a comprehensive RNA sequencing analysis and validated the differentially expressed genes (DEGs) with quantitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Transcriptome technology has been used to obtain detailed information on the expression of genes in other species of nematodes. In Bursaphelenchus xylophilus and Pelodera strongyloides, the average clean reads of each treatment were 50.8 and 47.5 million, respectively (Wang et al, 2019;Zhang et al, 2019). In previous studies on the transcriptome of S. carpocapsae, nearly 15 million clean reads were obtained, and 95% of the reads were mapped to the genome using the Illumina platform.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome technology has been used to obtain detailed information on the expression of genes in other species of nematodes. In Bursaphelenchus xylophilus and Pelodera strongyloides, the average clean reads of each treatment were 50.8 and 47.5 million, respectively (Wang et al, 2019;Zhang et al, 2019). In previous studies on the transcriptome of S. carpocapsae, nearly 15 million clean reads were obtained, and 95% of the reads were mapped to the genome using the Illumina platform.…”
Section: Discussionmentioning
confidence: 99%
“…Primer 6.0 software was used to design the primers and completed by Sangon Biotech (Shanghai, China) (Additional le 9). Bx28S and Actin gene were selected as the housekeeping gene [52]. Agilent Technologies Mx3000P was used for real-time PCR detection, and qPCR was performed following the protocol provided by the TaKaRa One-Step RT-PCR Kit (Baori medical technology (Beijing) co., LTD, Beijing, China) and compared to using the threshold cycle (-ΔΔCt) method of gene expression.…”
Section: Validation Of Gene Expression By Qrt-pcrmentioning
confidence: 99%
“…Researchers have found that this mechanism is regulated by many genes, including those associated with the cyclic guanosine phosphate (cGMP) pathway, cell autophagy pathway [ 38 ], and G protein signaling pathway [ 39 ], and have assessed the low-temperature response mechanism of PWNs. When the expression of the daf-11 and BxATG8 genes was inhibited, the survival and reproductive ability of PWNs at low temperatures decreased [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%